Source, migration, distribution, toxicological effects and remediation technologies of arsenic in groundwater in China - Zhen Wang; Hua-ming Guo; Hai-yan Liu; Wei-min Zhang (China Geology, 2023)
ABSTRACT: Groundwater with high arsenic (As) content seriously threatens human life and health. Drinking high-As groundwater for a long time will lead to various pathological changes such as skin cancer, liver cancer, and kidney cancer. High-As groundwater has become one of the most serious environmental geological problems in China and even internationally. This paper aims to systematically summarize the sources, migration, distribution, toxicological effects, and treatment techniques of As in natural groundwater in China based on a large number of literature surveys. High-As groundwater in China is mainly distributed in the inland basins in arid and semi-arid environments and the alluvial and lacustrine aquifers in river deltas in humid environments, which are in neutral to weakly alkaline and strongly reducing environments. The content of As in groundwater varies widely, and As(III) is the main form. The main mechanism of the formation of high-As groundwater in China is the reduced dissolution of Fe and Mn oxides under the action of organic matter and primary microorganisms, alkaline environment, intense evaporation and concentration, long-term water-rock interaction, and slow groundwater velocity, which promote the continuous migration and enrichment of As in groundwater. There are obvious differences in the toxicity of different forms of As. The toxic of As(III) is far more than As(V), which is considered to be more toxic than methyl arsenate (MMA) and dimethyl arsenate (DMA). Inorganic As entering the body is metabolized through a combination of methylation (detoxification) and reduction (activation) and catalyzed by a series of methyltransferases and reductases. At present, remediation methods for high-As groundwater mainly include ion exchange technology, membrane filtration technology, biological treatment technology, nanocomposite adsorption technology, electrochemical technology, and so on. All the above remediation methods still have certain limitations, and it is urgent to develop treatment materials and technical means with stronger As removal performance and sustainability. With the joint efforts of scientists and governments of various countries in the future, this worldwide problem of drinking-water As poisoning will be solved as soon as possible. This paper systematically summarizes and discusses the hot research results of natural high-As groundwater, which could provide a reference for the related research of high-As groundwater in China and even the world.©2023 China Geology Editorial Office.